Lack of plakoglobin impairs integrity and wound healing in corneal epithelium in mice. (November 2018) - Kokado, Masahide; Miyajima, Masayasu; Okada, Yuka; Ichikawa, Kana; Yamanaka, Osamu; Liu, Chia-Yang; Kao, Winston; Shou, Weinian; Saika, Shizuya
Abstract We generated cornea-specific plakoglobin (Jup ; junctional plakoglobin) knockout mice in order to investigate the function of plakoglobin on the maintenance of the homeostasis of corneal epithelium in mice. Cornea epithelium-specific conditional knockouts (Jup CEΔ/CEΔ ) (cKO) were obtained by breeding keratin12-Cre (Krt12-Cre ) mice toJup -floxed (Jup f/f ) mice. Light and transmission electron microscopic and immunohistochemical analyses were carried out to determine consequence of the loss of plakoglobin on maintaining corneal epithelium integrity under mechanical stress, e.g., brushing and wound healing. Immunohistochemistry analysis demonstrated that, althoughJup ablation did not affect BrdU incorporation, basal cell-like cells labeled for keratin 14 were ectopically present in the supra-basal layer in mutant corneal epithelium, suggestive of altered cell differentiation. Plakoglobin-deficient epithelium exhibits increased fragility against mechanical intervention when compared to wild-type controls under identical treatment. Closure of an epithelial defect was significantly delayed inJup CEΔ/CEΔ epithelium. Our findings indicate that the lack of plakoglobin significantly affects corneal epithelium differentiation, as well as its structural integrity. Plakoglobin is essential to the maintenance of the structure of the corneal epithelium and its wound healing. Homeostasis of the corneal epithelium is critical in exerting a barrier function to noxious external stimuli. This study shows that that plakoglobin, a member of the catenin protein family, is essential to the maintenance of homeostasis of the corneal epithelium in mice. Corneal epithelium-specific deletion of the plakoglobin gene impairs tissue integrity against mechanical intervention and also suppresses wound healing without affecting cell proliferation.